Intra-cardiac thrombus in antiphospholipid antibody syndrome: An unusual cause of fever of unknown origin with review of literature. Issue 5 (November 2016) - Dhibar, Deba Prasad; Sahu, Kamal Kant; Varma, Subhash Chander; Kumari, Savita; Malhotra, Pankaj; Mishra, Anand Kumar; Vaiphei, Kim; Khanal, Suraj; Suri, Vikas; Singhal, Manphool
Abstract: Classically, antiphospholipid antibody syndrome (APS) presents with recurrent episodes of vascular thrombosis and abortions. For APS to present as fever of unknown origin (FUO) is a rare phenomenon. We present an interesting case of FUO who on workup was found to have primary APS with right atrial thrombus and chronic pulmonary thromboembolism (PTE). Fever resolved completely with anticoagulation therapy and surgical removal of the intra-cardiac thrombus. Although rare, APS should be considered in any case of FUO with prolonged activated partial thromboplastin time and/or thrombocytopenia. We also take this opportunity to briefly review 28 cases of APS with intra-cardiac thrombus reported to date in the medical literature. <Learning objective: Primary antiphospholipid antibody syndrome (APS) presenting as fever of unknown origin (FUO) is rare. APS should be kept in the differential diagnosis in any case of FUO with prolonged activated partial thromboplastin time or thrombocytopenia. Intra-cardiac thrombus is more frequently associated with primary APS as compared to secondary APS.>